A Conceptual Model for the Imaginary: The Role of Symbols - Ciocoiu, Eugenia (Journal for the study of religions and ideologies, 2020)
In life, decisions are not only taken by considering logical reasoning, but they are influenced by images, symbols, and myths. Moreover, in our multicultural and multiracial societies, we must express ourselves with attention, to use careful comparisons and especially neutral expressions. Symbols multiply the effect of words, and consequently, the risk of saying something wrong is increased. Also, if each person one discusses with will know how to decode your words is a wrong assumption. The symbols mentioned are also influenced by other factors, and they are part of a more comprehensive concept, namely the imaginary. This study is a conceptual review of the imaginary concept. There are many disciplines that study the imaginary, and many definitions for it, given by researchers coming from all fields, but there are few papers that explain how the imaginary is formed and how it influences our lives. By reviewing the literature, we have identified major limitations of the theories and models that treat the imaginary. Studying all those studies was useful for us because from the beginning we wanted to understand how the imaginary is formed and how it can be decoded, so we developed our own framework. The key conclusion of this paper is that symbols are a useful concept for understanding imaginary, since they can be seen both as forms of communication of the intangible culture, but also as productions of the imaginary. By settling symbols in the middle of our conceptual model, imaginary can be easier understood and further used in other scientific investigations.